Control of dynamic cell behaviors during angiogenesis and anastomosis by Rasip1 - Lee Minkyoung; Betz Charles; Yin Jianmin; Paatero Ilkka; Schellinx Niels; Carte Adam N.; Wilson Christopher W.; Ye Weilan; Affolter Markus; Belting Heinz-Georg (COMPANY BIOLOGISTS LTD, 2022)
Organ morphogenesis is driven by a wealth of tightly orchestrated cellular behaviors, which ensure proper organ assembly and function. Many of these cell activities involve cell-cell interactions and remodeling of the F-actin cytoskeleton. Here, we analyze the requirement for Rasip1 (Ras-interacting protein 1), an endothelial-specific regulator of junctional dynamics, during blood vessel formation. Phenotype analysis of rasip1 mutants in zebrafish embryos reveals distinct functions of Rasip1 during sprouting angiogenesis, anastomosis and lumen formation. During angiogenic sprouting, loss of Rasip1 causes cell pairing defects due to a destabilization of tricellular junctions, indicating that stable tricellular junctions are essential to maintain multicellular organization within the sprout. During anastomosis, Rasip1 is required to establish a stable apical membrane compartment; rasip1 mutants display ectopic, reticulated junctions and the apical compartment is frequently collapsed. Loss of Ccm1 and Heg1 function mimics the junctional defects of rasip1 mutants. Furthermore, downregulation of ccm1 and heg1 leads to a delocalization of Rasip1 at cell junctions, indicating that junctional tethering of Rasip1 is required for its function in junction formation and stabilization during sprouting angiogenesis.